Preservice and inservice teachers’ views on digital tools for diverse learners in mathematics education - Meaney, Tamsin; Huru, Hilja L.; Kvivesen, Mona (NOMAD Nordic Studies in Mathematics Education, 2023)
Although teachers are expected to use digital tools in their mathematics teaching in many countries, little is known about preservice and inservice teachers’ digital competence, especially in relationship to specific groups of school students. Results from a survey of 394 preservice teachers and 61 inservice teachers, at three Norwegian institutions, provide information on how they considered different digital tools would support differentiated teaching, related to a student’s mathematical progress, and in multilingual classes. The results suggest that preservice and inservice teachers evaluated similarly the usefulness of different digital tools for differentiated mathematics teaching and in multilingual classrooms. However, for the majority of tools, the standard deviations indicate that the responses were somewhat spread, suggesting uncertainty in how they could use digital tools to support specific groups of students.